Bioassay-Guided Isolation of an Antibacterial Flavone and Cytotoxicity of the Leaf Extracts of Vitex rivularis Gurke (Lamiaceae) (Nigerian Journal of Pharmaceutical Research, 2022)
Background:The global challenge of resistance to several antibacterial agents has necessitated the continuous search for new antibacterial molecules. Natural products have proven to be a major source of new therapies for infections.Objectives:This study aimed at investigating the antibacterial and cytotoxicity activities of Vitex rivularis leaf extract and isolate its bioactive principle based on its local application in the treatment of bacterial infections. Materials and Methods: Methanol extract was tested against Escherichia coli ATCC 25922, Bacillus subtilis ATCC 6638, Staphylococcus aureus ATCC 59232, Proteus mirabilis ATCC 15290 and Pseudomonas aeruginosa ATCC 15442. Cytotoxicity activity of the crude extract was done using Brine Shrimp Lethality Assay (BSLA). Crude methanolic extract was subjected to column chromatography on silica gel and that afforded eight fractions (F1 – F8). The pooled fractions were monitored for antimicrobial activity against Escherichia coli and Bacillus subtilis. Minimum inhibitory concentration (MIC) of the crude and the most active fraction were determined by agar-dilution method using Gentamicin as the positive control. Fraction 7 was purified by recrystallisation in ethyl acetate to obtain Compound F7. The isolated bioactive compound was characterized by spectroscopic data (IR, 1H and 13C NMR, COSY, HMQC).Results:The MIC of the extract and isolated compound, F7, were between 0.25-0.50 mg/ml on E. coli and B. subtilis. Cytotoxicity activity showed LC50 of leaf extract to be 168.66µg/ml. The structure of the isolated bioactive compound was confirmed to be 5-hydroxy-3',4',6,7-tetramethoxyflavoneConclusion:The observed antibacterial activity of Vitex rivularis leaf extract justified the traditional use of the plant’s leaf in the treatment of bacterial infections by local users. The isolated compound can serve as a lead compound in the development of new antimicrobials agents.